Livestock for sale : animal husbandry in a Roman frontier zone : the case study of the civitas Batavorum - Groot, Maaike (Amsterdam archaeological studies, 2016)
"The civitas Botavorum is located on the northwestern frontier of the Roman empire. Following a long tradition of archaeological research, rescue archaeology has enormously increased the number of excavations in the last fifteen years. The quality of the data now available, particularly with regard to rural settlement, is excellent. This study investigates animal husbandry and food production. On the one hand, it uses zooarchaeological data to answer broader economic questions and to trace economic developments in a Roman frontier province. On the other hand, it is a regional synthesis and includes all zooarchaeological data for the region."--Page 4 of cover